Penegakan Hukum Pertambangan Tanpa Izin Berbasis Transendental - Sanawiah Sanawiah; Istani Istani (IAHN Tampung Penyang Palangka Raya, 2022)
Unlicensed Mining is a criminal act. In the realm of law enforcement, it is very closely related to the social and economic problems of the poor people around mining areas, thus creating a dilemma for law enforcement officers in processing unlicensed mining cases. The research method used was juridical-normative. The presence of PETI has an impact on the loss of state treasury revenues, environmental damage, mining accidents, an unfavorable investment climate, and waste of mineral resources. The law enforcement policy is the implementation of utilitarianism policy and punishment policy as the ultimum remedium. The law enforcement officers must consider non-penal law enforcement against PETI, and the government must provide guidance and supervision so that PETI can turn into a legitimate business.